2022
DOI: 10.1021/acs.jmedchem.2c01418
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fluorinated Peptoid-Based Histone Deacetylase (HDAC) Inhibitors for Therapy-Resistant Acute Leukemia

Abstract: Using a microwave-assisted protocol, we synthesized 16 peptoid-capped HDAC inhibitors (HDACi) with fluorinated linkers and identified two hit compounds. In biochemical and cellular assays, 10h stood out as a potent unselective HDACi with remarkable cytotoxic potential against different therapy-resistant leukemia cell lines. 10h demonstrated prominent antileukemic activity with low cytotoxic activity toward healthy cells. Moreover, 10h exhibited synergistic interactions with the DNA methyltransferase inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 72 publications
(156 reference statements)
2
9
0
Order By: Relevance
“…This effect was more pronounced when a fluorine atom was introduced in meta -position to the hydroxamic acid ( A5 and B5 ). The beneficial effect of a fluorinated benzyl linker with regard to HDAC6 selectivity is in line with recent results disclosed by us and others [ 38 , 43 , 44 ]. Notably, the benzimidazole-fluorobenzyl-based compounds A6 (IC 50 HDAC1 = >2.80 µM; IC 50 HDAC6 = 0.011 µM; SI = >254) and B6 (IC 50 HDAC1 = 0.829 µM; IC 50 HDAC6 = 0.005 µM; SI = 166) demonstrated potent and highly selective HDAC6 inhibition, which is in excellent agreement with a recent report on HDAC6-selective proteolysis-targeting chimeras (PROTACs) [ 45 ]).…”
Section: Resultssupporting
confidence: 89%
“…This effect was more pronounced when a fluorine atom was introduced in meta -position to the hydroxamic acid ( A5 and B5 ). The beneficial effect of a fluorinated benzyl linker with regard to HDAC6 selectivity is in line with recent results disclosed by us and others [ 38 , 43 , 44 ]. Notably, the benzimidazole-fluorobenzyl-based compounds A6 (IC 50 HDAC1 = >2.80 µM; IC 50 HDAC6 = 0.011 µM; SI = >254) and B6 (IC 50 HDAC1 = 0.829 µM; IC 50 HDAC6 = 0.005 µM; SI = 166) demonstrated potent and highly selective HDAC6 inhibition, which is in excellent agreement with a recent report on HDAC6-selective proteolysis-targeting chimeras (PROTACs) [ 45 ]).…”
Section: Resultssupporting
confidence: 89%
“…In contrast, this is hindered in class I HDAC (e.g., HDAC1) because the Ser531 is exchanged by an Arg. These results of Sandrone et al [ 83 ] were similarly confirmed in the study of Reßing, Schliehe-Diecks et al, where an increased inhibition of HDAC4 (HDAC class IIa) was detected due to compounds with a fluorinated linker [ 84 ].…”
Section: Biological Significance and Purpose Of Fluorination In Hdacissupporting
confidence: 56%
“…63 In vitro inhibitory activities against HDAC4 were measured using a previously published protocol with slight modifications. 67 For compounds and controls, threefold serial dilutions of the respective DMSO-stock solution in assay buffer (50 mM Tris−HCl, pH 8.0, 137 mM NaCl, 2.7 mM KCl, 1.0 mM MgCl 2 •6 H 2 O, 5 mg/mL BSA) were prepared and 5.0 μL of this serial dilution was transferred into OptiPlate-96 black microplates (PerkinElmer). Then, 25 μL of assay buffer and 10 μL of enzyme solution (human recombinant HDAC1 (BPS Bioscience, Catalog no.…”
Section: -[2-(benzylamino)-2-oxoethyl]-n-{4-[5-(difluoromethyl)-134ox...mentioning
confidence: 99%